(untitled) (Research, Society and Development, 2020)
The pineapple Pearl (Pineapple comosus) is a typical Brazilian fruit, known for its peculiar and remarkable sensory characteristics, rich in vitamins, minerals. Peppers of the genus Capsicum, have the preference of the world consumer either in fresh or processed form, being excellent source of natural antioxidants, carotenoids and phenolic compounds. The importance of spices in human life is great, they not only enrich the taste of food but can influence human physiology and biochemistry. Thus, the objective of this work was to evaluate the bioactive compounds present in both fruits and antioxidant activity by the DPPH method, as well as to verify the correlations between them through Pearson correlation. The fruits under study had a high vitamin C content (56.46 to 52.29 mg of ascorbic acid / 100g of sample for pineapple and pepper respectively), besides moderate antioxidant action by the DPPH method (12.38 and 17.19 g fruit / g DPPH, values expressed by EC50 result). However, the study shows that the antioxidant capacity by the DPPH method has no significant correlation with the other bioactive compounds of both fruits.